Economic Growth, Inequalities and Poverty in Slovakia from 2005 to 2015 (the Analysis of Relations and Contexts at a Regional Level) - Michálek, Anton; Výbošťok, Ján (European Spatial Research and Policy, 2018)
Poverty rate is influenced by numerous factors. The determining ones are economic growth and the distribution of its effects. This article is therefore focused on the analysis of these effects and their relationship, as well as their influence on poverty at a regional level (NUTS 3, ‘kraj’). For the analysis of interactions between growth and distribution in correlation to poverty reduction, the Bourguignon model (the Poverty-Growth-Inequality triangle) and the growth incidence curve (GIC) were used. It was found that economic growth positively influences income inequalities as well as decreases the share of population under the poverty threshold in all regions. However, the development differs across regions. Based on the development and tendencies of the gross domestic product (GDP), income distribution and poverty it is obvious that economically strong regions (or their populations) dealt better with poverty during the crisis period.